IoT-based cloud monitoring system for building fires - Pan Guanhong; Xie Yanzhang; Yang Qingping (International Journal of Metrology and Quality Engineering)
This paper presents an IoT (Internet of Things) based smart building fire cloud monitoring system to enhance fire safety in smart buildings. It integrates low-cost sensors and real-time video surveillance for real-time environmental data collection. Data are uploaded to the cloud for remote monitoring via a custom web interface. The system features an artificial neural network model that reduces computational complexity and response time, achieving >95% accuracy in fire prediction. It assists in planning evacuation routes based on fire location, enhancing safety and efficiency. Laboratory and field tests confirm reliable performance, and the novel system will find applications in smart fire detection and prevention.